Lady and the Tramp II Scamp's adventure - Rooney, Darrell; Roussel, Jeannine; Motz, Bill.; Roth, Bob.; Wolf, Scott, 1968-; Milano, Alyssa; Palminteri, Chazz; Trenbirth, Steve; Warter, Fred.; Schaefer, Robert; Edmunson, Susan; Manchester, Melissa; et al. (Burbank, Calif. : Walt Disney Home Video : Distributed by Buena Vista Home Entertainment, 2000)
Scamp, who is being raised by Lady and Tramp, longs for freedom, but when he ventures far from home and meets Angel, a stray, he is torn between a world of adventure and the family he has left behind.
Director of animation, Steve Trenbirth ; art directors, Fred Warter, Robert Schaefer ; supervising film editor, Susan Edmunson ; music & lyrics by Melissa Manchester, Norman Gimbel ; music score by Danny Troob.
Scott Wolf (Scamp), Alyssa Milano (Angel), Chazz Palminteri (Buster).
Rated G.
VHS format; hi-fi stereo, Dolby surround.
Closed-captioned.
Keywords: Dogs -- Juvenile drama; Dogs; Children's films; Films for the hearing impaired; Animated films; Feature films